A 3D Hierarchical Host with Enhanced Sodiophilicity Enabling Anode‐Free Sodium‐Metal Batteries. Issue 14 (1st March 2022) - Lee, Kyungbin; Lee, Young Jun; Lee, Michael J.; Han, Junghun; Lim, Jeonghoon; Ryu, Kun; Yoon, Hana; Kim, Byung‐Hyun; Kim, Bumjoon J.; Lee, Seung Woo
Abstract: Sodium‐metal batteries (SMBs) are considered as a compliment to lithium‐metal batteries for next‐generation high‐energy batteries because of their low cost and the abundance of sodium (Na). Herein, a 3D nanostructured porous carbon particle containing carbon‐shell‐coated Fe nanoparticles (PC‐CFe) is employed as a highly reversible Na‐metal host. PC‐CFe has a unique 3D hierarchy based on sub‐micrometer‐sized carbon particles, ordered open channels, and evenly distributed carbon‐coated Fe nanoparticles (CFe) on the surface. PC‐CFe achieves high reversibility of Na plating/stripping processes over 500 cycles with a Coulombic efficiency of 99.6% at 10 mA cm –2 with 10 mAh cm –2 in Na//Cu asymmetric cells, as well as over 14 400 cycles at 60 mA cm –2 in Na//Na symmetric cells. Density functional theory calculations reveal that the superior cycling performance of PC‐CFe stems from the stronger adsorption of Na on the surface of the CFe, providing initial nucleation sites more favorable to Na deposition. Moreover, the full cell with a PC‐CFe host without Na metal and a high‐loading Na3 V2 (PO4 )3 cathode (10 mg cm –2 ) maintains a high capacity of 103 mAh g –1 at 1 mA cm –2 even after 100 cycles, demonstrating the operation of anode‐free SMBs. Abstract : Hierarchically porous carbon particles with open channels allow rapid Na‐ion flux, and evenly distributed carbon‐coated Fe nanoparticles on the carbon surface induce uniform Na deposition owing to the enhanced Na binding energy. The hierarchical host enables superior cycling performance as Na‐metal anodes under extremely high current conditions as well as demonstration of anode‐free sodium‐metal batteries.